Certain new class of concave functions defined by sălăgean differential operator - Ibtisam Aldawish; Maslina Darus (Penerbit Universiti Kebangsaan Malaysia, 2013)
In this article, we introduce a class of concave analytic functions SnC0(α) defined by Sălăgean differential operator. We study some properties like coefficient inequalities, distortion theorems and extreme points for this class.